ANALYTIC HIERARCHICAL METHOD APPLIED TO BRUSH CUTTER BLADE SELECTION - Chucheep, Thiensak; Mahathaninwong, ์Narissara; Janudom, Somjai (The South African Journal of Industrial Engineering, 2019)
The objective of this work was to use the analytic hierarchic process (AHP) to select the best replacement brush cutter blades. The seven decision criteria of the AHP included three mechanical property criteria and four commercial data criteria. The mechanical property criteria were based on wear rate, impact toughness, and hardness, all of which were tested, while the four commercial data criteria were set on price, weight, packaging information, and product distribution, which were surveyed. Four replacement brush cutter steel blades of types 65C, 72C, 73C, and 81C were included. The best alternative was the 65C steel blade according to the AHP method.